Clostridium difficile ribotype 027 is not evenly distributed in Hesse, Germany. (August 2016) - Arvand, Mardjan; Bettge-Weller, Gudrun
Abstract: Clostridium difficile -isolates associated with CDI in different healthcare facilities in Hesse were analysed. The most common ribotypes were 001 (31.1%) and 027 (27.0%). The proportion of ribotype 027 among regional C. difficile -isolates was 10.8% in North Hesse, 17.2% in Middle Hesse, and 33.5% in the Rhine-Main Metropolitan Area. In the latter region, ribotype 027 was the most prevalent ribotype. Highlights: Clostridium difficile ribotype 027 is unevenly distributed in Hesse. Ribotype 027 has become the most common C. difficile strain in the Rhine-Main metropolitan area. Clinicians and infection control specialists should be aware of an increased risk of outbreaks by ribotype 027 in Germany. Establishment of a national surveillance program for CDI in combination with microbiological data is necessary for prevention of CDI in Germany. Timely availability of typing results is necessary for cluster investigation and identification of possible transmissions.